Impact of surgical technique (open vs laparoscopic vs robotic‐assisted) on pathological and biochemical outcomes following radical prostatectomy: an analysis using propensity score matching - Magheli, Ahmed; Gonzalgo, Mark L.; Su, Li‐Ming; Guzzo, Thomas J.; Netto, George; Humphreys, Elizabeth B.; Han, Misop; Partin, Alan W.; Pavlovich, Christian P. (BJU international, 2011)
Study Type – Therapy (case series) Level of Evidence 4 What’s known on the subject? and What does the study add? Thus far, no institution has investigated the impact of the most commonly used surgical techniques – open, laparoscopic and robotic radical prostatectomy – on biochemical outcome. However, recent data from large meta‐analysis suggest that the impact of the chosen surgical technique on biochemical outcome is minimal and statistically not relevant. We are the first to apply the method of propensity score matching in the urology literature to compare three different surgical techniques. This method is intended to simulate a randomized trial which is unlikely to be undertaken for radical prostatectomies. We confirmed previous data that the surgical technique does not seem to have an impact on biochemical outcome following radical prostatectomy. OBJECTIVE • To investigate a single institution experience with radical retropubic prostatectomy (RRP), laparoscopic radical prostatectomy (LRP) and robot‐assisted radical prostatectomy (RARP) with respect to pathological and biochemical outcomes. PATIENTS AND METHODS • A group of 522 consecutive patients who underwent RARP between 2003 and 2008 were matched by propensity scoring on the basis of patient age, race, preoperative prostate‐specific antigen (PSA), biopsy Gleason score and clinical stage with an equal number of patients who underwent LRP and RRP at our institution. • Pathological and biochemical outcomes of the three cohorts were examined. RESULTS • Overall positive surgical margin rates were lower among patients who underwent RRP (14.4%) and LRP (13.0%) compared to patients who underwent RARP (19.5%) (P= 0.010). There were no statistically significant differences in positive margin rates between the three surgical techniques for pT2 disease (P= 0.264). • In multivariate logistic regression analysis, surgical technique (P= 0.016), biopsy Gleason score (P < 0.001) and preoperative PSA (P < 0.001) were predictors of positive surgical margins. • Kaplan–Meier analysis did not show any statistically significant differences with respect to biochemical recurrence for the three surgical groups. CONCLUSIONS • RRP, LRP and RARP represent effective surgical approaches for the treatment for clinically localized prostate cancer. A higher overall positive SM rate was observed for the RARP group compared to RRP and LRP; however, there was no difference with respect to biochemical recurrence‐free survival between groups. • Further prospective studies are warranted to determine whether any particular technique is superior with regard to long‐term clinical outcomes.